Terahertz Sources Based on Metrological‐Grade Frequency Combs. Issue 2 (30th November 2022) - Riccardi, Elisa; Pistore, Valentino; Consolino, Luigi; Sorgi, Alessia; Cappelli, Francesco; Eramo, Roberto; De Natale, Paolo; Li, Lianhe; Davies, Alexander Giles; Linfield, Edmund H.; Vitiello, Miriam S.
Abstract: Broadband metrological‐grade frequency comb (FC) synthesizers with a rich number of phase locked modes are the ideal sources for quantum sensing and quantum metrology. At terahertz (THz) frequencies, electrically pumped quantum cascade lasers (QCLs) have shown quantum‐limited frequency noise operation, phase/frequency absolute referencing and self‐starting FC operation, albeit over a rather restricted dynamic range, governed by the nature of the quantum gain media that entangles group velocity dispersion at the different bias points. Here, a technological approach is conceived to achieve FC operation over the entire available gain bandwidth at THz frequencies. The intracavity light intensity of a multistack QCL, inherently showing a giant Kerr nonlinearity, is altered by increasing the mirror losses of its Fabry‐Perot cavity through coating the back facet with an epitaxially‐grown multilayer graphene film. This enables a frequency modulated THz FC showing a proliferation of emitted modes over the entire gain bandwidth and across more than 60% of its operational range, with ≈0.18 mW per mode optical power. The QCL FC is then experimentally characterized to assess its phase coherence, reconstructing its intensity emission profile, instantaneous frequency, and electric field, thus proving its metrological nature. Abstract : A record dynamic range frequency‐modulated terahertz frequency comb is engineered through coating the back facet of a semiconductor heterostructure laser with an epitaxially grown multilayer graphene film.